Synthesis of biologically active heterocyclic compounds and their fused derivatives - Fatma Alzahraa Omar Alfarouk Abdelazim; Raafat Mohareb (Cairo : Fatma Alzahraa Omar Alfarouk Abdelazim, 2009)
This research work is concerned with the synthesis of novel heterocyclic precursors and their employment in synthesizing new pyrazoles thiazoles pyridines pyrimidines and triazines exhibiting anti-depressive activity and acute toxicity in mice. Some of those precursors are 2-Amino-5,6-dihydro-4H-cyclopenta[b]thiophene-3-carbonitrile(3a in part I), 2-Cyano-N
Thesis (Ph.D.) - Cairo University - Faculty of Science - Department of Organic Chemistry
Issued also as CD
Keywords: Cyclopentanone; Thiophenes; Triazines